2011
DOI: 10.5578/tt.2139
|View full text |Cite
|
Sign up to set email alerts
|

Semirigid thoracoscopy in the diagnosis of pleural effusion: first four cases in Turkey

Abstract: Medical thoracoscopy is a valuable tool in the management

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Additionally, many chest physicians are more comfortable learning to use the semi-rigid thoracoscope because it resembles the flexible bronchoscope in design and operation. Ernst et al first reported their experience with semi-rigid thoracoscopy in 2002, and since then there have been multiple trials in a variety of settings noting its diagnostic and therapeutic efficacy (26)(27)(28)(29)(30)(31). The diagnostic yield of semi-rigid thoracoscopy was well-characterized by Agarwal et al in their meta-analysis of 17 individual trials involving this approach in 755 patients (32).…”
Section: Techniques: Rigid Vs Semi-rigid Approachmentioning
confidence: 99%
“…Additionally, many chest physicians are more comfortable learning to use the semi-rigid thoracoscope because it resembles the flexible bronchoscope in design and operation. Ernst et al first reported their experience with semi-rigid thoracoscopy in 2002, and since then there have been multiple trials in a variety of settings noting its diagnostic and therapeutic efficacy (26)(27)(28)(29)(30)(31). The diagnostic yield of semi-rigid thoracoscopy was well-characterized by Agarwal et al in their meta-analysis of 17 individual trials involving this approach in 755 patients (32).…”
Section: Techniques: Rigid Vs Semi-rigid Approachmentioning
confidence: 99%
“…The effect of these risk-increasing factors can be reduced with necessary additional support. In a study in which 355 patients who underwent MT were compared after dividing them into two groups as high-risk patients and normal-risk patients for complications, the most common complication was found to be pain (12.3%) in the high-risk group, the rate of which was significantly higher than that found the normal-risk group (27).…”
Section: Medical Thoracoscopy For Diagnostic Purposementioning
confidence: 99%
“…On the other hand, semirigid thoracoscope was first used in the İstanbul Yedikule Chest Diseases and Chest Surgery Training and Research Hospital (27).…”
Section: Historymentioning
confidence: 99%